A paraventricular hypothalamic nucleus input to ventral of lateral septal nucleus controls chronic visceral pain. Issue 3 (19th March 2023) - Li, Yong-Chang; Wang, Qian; Li, Meng-Ge; Hu, Shu-Fen; Xu, Guang-Yin
Abstract : Supplemental Digital Content is Available in the Text. Paraventricular hypothalamic CaMKIIα-positive neurons input to ventral of lateral septal CaMKIIα-positive neurons controls chronic visceral pain. Abstract: Irritable bowel syndrome is a functional gastrointestinal disorder characterized by chronic visceral pain with complex etiology and difficult treatment. Accumulated evidence has confirmed that the sensitization of the central nervous system plays an important role in the development of visceral pain, whereas the exact mechanisms of action of the neural pathways remain largely unknown. In this study, a distinct neural circuit was identified from the paraventricular hypothalamic (PVH) to the ventral of lateral septal (LSV) region. This circuit was responsible for regulating visceral pain. In particular, the data indicated that the PVH CaMKIIα-positive neurons inputs to the LSV CaMKIIα-positive neurons were only activated by colorectal distention rather than somatic stimulations. The PVH-LSV CaMKIIα + projection pathway was further confirmed by experiments containing a viral tracer. Optogenetic inhibition of PVH CaMKIIα + inputs to LSV CaMKIIα-positive neurons suppressed visceral pain, whereas selective activation of the PVH-LSV CaMKIIα + projection evoked visceral pain. These findings suggest the critical role of the PVH-LSV CaMKIIα + circuit in regulating visceral pain.